Effects of Irbesartan and Amlodipine Besylate Tablets on the Intestinal Microflora of Rats With Hypertensive Renal Damage - Yu, Jing; Ma, Yan; He, Xin; Long, Xiao Na; Xu, Jun; Wang, Lei; Feng, Zhi-Peng; Peng, Hong-Ying (Frontiers in Pharmacology, 2022)
Objective: The present study aimed to investigate the effects of irbesartan and amlodipine besylate tablets on the intestinal microflora of rats with hypertensive renal damage. Method: Eighteen 12-week-old male spontaneous hypertensive rats were randomly divided into three groups. The Ai-HDG group was given irbesartan at 15 mg/kg per day by gavage, the Ci-HDG group was given amlodipine besylate tablets at 1 mg/kg per day by gavage, and the Wi-HDG group, i.e., the control, was given the same dose of distilled water per day by gavage. The treatment lasted for six weeks. Six 12-week-old male Wistar–Kyoto  rats were used as the reference group. Bacterial DNA was extracted from the feces of all the rats for high-throughput sequencing before and after the experiment. Operational taxonomic units were used to analyze the species of the intestinal flora, and the alpha diversity index was used to analyze the diversity. The relative abundance of the intestinal microflora in each group of rats was therefore analyzed at the phylum and genus levels. Results: Compared with the Wi-HDG group, the alpha diversity of the Ai-HDG group increased (P < 0.05), while in the Ci-HDG group, only the Shannon index increased significantly. At the phylum level, compared with the control group, in the Ai-HDG and Ci-HDG groups, Firmicutes (F) decreased, Bacteroides (B) increased, and the F/B ratio decreased (P < 0.05). At the genus level, compared with the Wi-HDG group, the Ai-HDG and Ci-HDG groups did not show a significantly delayed decline in lactic acid bacteria. However, in the Ai-HDG group, the relative abundance of Bifidobacteria increased. Conclusions: After the administration of irbesartan and amlodipine besylate, the disorder of intestinal flora in the rats with hypertensive renal damage improved. However, irbesartan was better than amlodipine besylate at improving the diversity of the intestinal flora in these rats.